PIRINSIP ITIKAD BAIK PEMEGANG POLIS DALAM PENGAJUAN KLAIM KEPADA PT AIA FINANCIAL: Principles of Good Faith of Policyholders in Submitting Claims to PT AIA - Al Qaeda Putra Nusantara; Siti Nurbaiti (Jurnal Hukum PRIORIS, 2024)
Insurance is an agreement between the insurer and the insured as the policy holder. Often in holding an insurance agreement raises a problem, one of which is in the case of a policyholder named Kim Joo Sang not providing true and accurate information regarding the condition of the object of coverage at the time of holding life insurance with PT AIA Financial as the insurer, thus causing rejection of the submission of insurance claims. The problem is whether the Policyholder in submitting a claim to PT AIA Financial has fulfilled the principle of good faith. This research uses normative research methods, is descriptive in nature, uses secondary data, data collection is done by means of literature studies, which are analyzed qualitatively and conclusions are drawn deductively. The results of the study illustrate that legally the policyholder has violated the principle of good faith which resulted in the rejection of the claim submitted by the policyholder to PT AIA Financial because it has violated the principle of good faith stipulated in Article 251 of the Commercial Code.